2017
DOI: 10.1109/tnsre.2017.2709756
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Kinematics Using Task-Independent Movement-Phase-Specific Encoding Models

Abstract: Neural decoders of kinematic variables have largely relied on task-dependent (TD) encoding models of the neural activity. TD decoders, though, require prior knowledge of the tasks, which may be unavailable, lack scalability as the number of tasks grows, and require a large number of trials per task to reduce the effects of neuronal variability. The execution of movements involves a sequence of phases (e.g., idle, planning, and so on) whose progression contributes to the neuronal variability. We hypothesize tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In addition, they implemented an extended model to decode multiple states, one for each reaching goal. In another study a four states (additional holding state) HMM was used to detect hidden neural states and so to develop a task independent decoder [57]. Here we used a simpler, but equally informative, Bayesian decoder to obtain posterior probabilities of free, delay and movement states.…”
Section: Encoding Of Task Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they implemented an extended model to decode multiple states, one for each reaching goal. In another study a four states (additional holding state) HMM was used to detect hidden neural states and so to develop a task independent decoder [57]. Here we used a simpler, but equally informative, Bayesian decoder to obtain posterior probabilities of free, delay and movement states.…”
Section: Encoding Of Task Progressmentioning
confidence: 99%
“…A large amount of evidence has already reported that single PPC neurons can encode both spatial (sensory) and non-spatial (cognitive) information [52,[57][58][59][60]. For example, attention toward a specific spatial location or toward non-spatial visual features modulate lateral intraparietal neurons [50,60,61], parietal reach region encodes both the target location and the movement intention [58,59].…”
Section: Different Parameters Encoded In the Same Circuit Is Advantag...mentioning
confidence: 99%
“…Point process methods have been used to analyze the spike train activity for a broad range of neural systems (Sarma et al, 2010, 2012; Saxena et al, 2010, 2012; Santaniello et al, 2012; Sumsky et al, 2017; Sumsky and Santaniello, 2018). A neural spike train can be treated as a stochastic series of random binary events (i.e., the spike times) continuously occurring in time, otherwise known as a point process (Truccolo et al, 2005; Coleman and Sarma, 2010; Sarma et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Most BCI implementations decode the movement intentions from motor cortex neuronal activity to control assistive devices (Collinger et al 2013, Shenoy et al 2013. Recently, studies have demonstrated the possibility to better guide iBCI effectors using discrete movement intentions (Fan et al 2014), states (Kao et al 2017, Sumsky et al 2017, transitions (Kang et al 2015), and goals (Andersen et al 2019) decoded from other cortical areas of the brain. In line with this strategy, our results show that spatial locations within a physical or virtual environment can be deciphered from the LPFC intracortical activity, possibly to assist in the control of intelligent wheelchairs.…”
Section: Decoding Of Space In the Primate Brainmentioning
confidence: 99%